Parallel Context-Free Languages - Skyum, Sven (DAIMI Report Series, 1974)
The relation between the family of context-free languages and the family of parallel context-free languages is examined in this paper. It is proved that the families are incomparable. Finally we prove that the family of languages of finite index is contained in the family of parallel context-free languages. Information and Control, 26 (1974) pp. 280-285.